Social protection and fight against poverty in Brazil, Colombia and Chile. Graduate from the PTC or get out of poverty? - Chiodi, Francesco (2018)
Review of the book Social protection and fight against poverty in Brazil, Colombia and Chile. Graduate from the PTC or get out of poverty?, Madrid: Programa EUROsociAL, 2015. Carlo Tassara (Editor), Antonio Ibarra y Luis Vargas Faulbaum.